Effect of a propionic acid bacterial inoculant on fermentation and aerobic stability of whole-plant corn silage - Bolsen, K.K.; Bonilla, D.R.; Huck, G.L.; Hart-Thakur, R.A.; Young, Matthew A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The effects of a strain of Propionibacterium shermanii, applied with and without lactic acid bacteria (LAB), on the fermentation and aerobic stability of whole-plant corn silage was determined using laboratory-scale silos. The addition of LAB increased the rate of fermentation, and all inoculated silages underwent a more efficient ensiling process than control silage. Only silages made with P. shermanii had measurable levels of propionic acid in the 90-day silages. Corn silages made with P. shermanii were more stable when exposed to air than control or LAB-inoculated silages.
Keywords: Beef; Silage; Aerobic spoilage; Inoculant; Propionic acid